Mold release agent for concrete molds
The mold release agent, comprising N-octylpyrrolidone, a base oil, and an antistatic agent, addresses the issues of conventional agents by improving releaseability, cleaning, smoothness, paint adhesion, and workability, resulting in higher quality concrete products.
Patent Information
- Application Number
- JP2024154001
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-12
- Filing Date
- 2024-09-06
- Publication Date
- 2025-03-25
AI Technical Summary
Conventional mold release agents for formwork suffer from insufficient releaseability, cleaning difficulties, surface unevenness, poor paint adhesion, and lower workability, which affect the quality and aesthetics of concrete products.
A mold release agent comprising N-octylpyrrolidone, a base oil with specific kinematic viscosity, and an antistatic agent, which improves releaseability, cleaning, smoothness, paint adhesion, and workability by enhancing self-leveling, reducing air bubbles, and ensuring excellent paint adhesion.
The mold release agent achieves excellent releaseability, easy cleaning, smooth surface finish, good paint adhesion, and improved workability, addressing the limitations of conventional agents and enhancing the quality of concrete products.
Smart Images

Figure 2025040961000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a release agent for a formwork. [Background technology]
[0002] Conventionally, concrete has been used in the construction of various structures such as houses, office buildings, etc. In order to give the concrete a desired shape, size, and strength, a process is generally carried out in which concrete material containing cement is poured into a formwork and allowed to harden within the formwork.
[0003] To facilitate the release of the hardened concrete from the form, a form release agent is conventionally applied to the inner surface of the form. Examples of form release agents include those containing mineral oil or animal and vegetable oil as a main component. In addition, for example, Patent Document 1 below discloses a form release agent for hydraulic compositions that contains the following component (A) or the following component (B) and has an aromatic hydrocarbon content of 5.0 mass% or less. Component (A): A compound represented by the following general formula (1A):
[0004] [ka]
[0005] (In the formula, R 1a is an alkyl group having 10 to 26 carbon atoms or an alkenyl group having 10 to 26 carbon atoms; R 2a is an alkyl group having 1 to 22 carbon atoms, an alkenyl group having 1 to 22 carbon atoms, or a hydroxyalkyl group having 1 to 22 carbon atoms; R 3a , R 4a are respectively an alkyl group having 1 to 3 carbon atoms or a hydroxyalkyl group having 1 to 3 carbon atoms, Y is an ethylene group or a propylene group, n is the number 0 or 1, and X - represents an anionic group derived from an anionic aromatic compound. Component (B): Two or more compounds represented by the following general formula (1B), wherein the two or more compounds are R1b are different, and at least one of the two or more compounds is R 1b R 11b or R 12b Compounds in which is an alkenyl group
[0006] [ka]
[0007] [In the formula, R 1b is R 11b or R 12b -[CONH-CH2CH2CH2] m R is a group represented by the formula: 11b R is an alkyl group having 14 to 22 carbon atoms or an alkenyl group having 14 to 22 carbon atoms. 12b is an alkyl group having 13 to 21 carbon atoms or an alkenyl group having 13 to 21 carbon atoms. m is an integer of 1 to 3. 2b and R 3b are each independently an alkyl group having 1 to 4 carbon atoms or -(C2H4O) p H. p is the average number of moles added, and R 2b and R 3b The sum of these is a number between 0 and 5. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2023-9801 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, conventional mold release agents have various problems as described below. (1) The release properties are insufficient. For example, when manufacturing precast concrete (hereafter referred to as PC) components, if a conventional formwork release agent is used, the release effect is insufficient, and pockmarks and air bubbles form on the surface of the demolded PC components, damaging their aesthetic appearance. In severe cases, it is necessary to repair them with repair materials. (2) Cleaning is insufficient. After the concrete has been removed from the formwork, it is necessary to clean the inner surface of the formwork. For this purpose, a spatula-shaped scraper or the like is used to scrape off any residue adhering to the inner surface of the formwork. However, some of the residue adheres firmly to the inner surface of the formwork, making it difficult to remove. (3) The smoothness is insufficient. As described above, the release effect of conventional formwork release agents is insufficient. In addition, due to the influence of air bubbles generated in the formwork after the concrete is poured and the insufficient effect of the formwork release agent, unevenness occurs on the surface of the concrete released from the formwork, making it difficult to obtain a sufficient smoothness, and impairing the design. (4) Poor paint adhesion. For example, after a PC component is demolded, a finishing material is usually applied, such as a paint, to enhance the design of the PC component surface. However, when a conventional formwork release agent is used, the formwork release agent remaining on the surface of the PC component inhibits adhesion between the PC component and the paint, and there is a risk that the paint may peel off over time. For this reason, it was necessary to carefully remove the release agent remaining on the concrete surface. Note that there is a trade-off between the demoldability of concrete and the adhesion of concrete to paint. (5) Poor workability. Conventional form release agents generally generate an odor that is unpleasant for workers, is detrimental to their health, and impairs the workability during form release.
[0010] An object of the present invention is to solve the above-mentioned problems in the conventional art. [Means for solving the problem]
[0011] The present invention is as follows. 1. (1) N-octylpyrrolidone, (2) a kinetic viscosity at 40°C of 30 to 120 mm2 and (3) an antistatic agent, which is capable of retaining design properties, cleanability, and paint adhesion. 2.(4) The form release agent according to 1 above, further comprising a diluent. 3.(5) When it is desired to further improve the release properties as a release aid, the form release agent described in 1 or 2 above containing a fluorine-based surfactant and / or a silicone-based surfactant is used. However, this is not absolutely necessary as it weakens the adhesion of the paint. 4. The release agent for form according to any one of 1 to 3 above, wherein, when the total amount of the release agent for form is taken as 100% by mass, the proportion of the (1) N-octylpyrrolidone is 1 to 10% by mass, the proportion of the (2) base oil is 40 to 90% by mass, the proportion of the (3) antistatic agent is 1 to 10% by mass, and the remainder is the (4) diluent and other additives. 5. The form release agent according to 3 above, wherein the proportion of the fluorine-based surfactant and / or silicone-based surfactant (5) is 0.1 to 5 mass % when the total amount of the form release agent is 100 mass %. 6. (1) N-octylpyrrolidone, (2) a kinetic viscosity at 40°C of 30 to 120 mm 2 and (3) an antistatic agent, and capable of producing a concrete product or mortar product having excellent smoothness. 7. A method for casting a hydraulic composition, comprising the steps of applying the form release agent according to any one of 1 to 6 above to an inner surface of a form, and casting a hydraulic composition thereon. Effect of the Invention
[0012] The release agent for forms of the present invention solves the above-mentioned problems of the prior art and exhibits excellent properties in terms of releasability, cleanability, smoothness, paint adhesion and workability.
[0013] The release agent for mold forms of the present invention is an emulsion type release agent, and the base oil contained therein has a specific viscosity range, so that the release agent for mold forms has a self-leveling property on the surface of, for example, a general-purpose steel mold form, and the release agent for mold forms can be easily and uniformly applied to the surface of the mold form. It can also be said that the base oil functions as a spreading agent. On the other hand, N-octylpyrrolidone is likely to be present on the surface of the formwork even after concrete has been poured, and the above-mentioned components contained in the formwork release agent of the present invention can provide excellent releasability. It can also be said that N-octylpyrrolidone functions as a spreading agent and an emulsifier. Furthermore, due to the above-mentioned improved self-leveling and releasability, slag is less likely to remain after the concrete is removed from the mold, and even if slag remains, it can be easily removed, thereby solving the problem of cleanability. In addition, the form release agent of the present invention has high wettability, for example, to the surface of a general-purpose steel form, and as a result, after concrete is poured, air pockets near the form surface are eliminated in the process of reducing free water as the concrete hardens and dries, and the generation of air bubbles on the surface of the demolded concrete is reduced. As a result, the surface of the demolded concrete is reduced in pits and air bubbles, providing sufficient smoothness. Furthermore, because of its high wettability, the agent spreads thinly over the surface of the form, making it possible to minimize the amount of release agent used. In addition, the form release agent of the present invention reduces the free water near the form surface as the concrete hardens, and when the water is almost gone, the hydrophobic component contained in the concrete acts to bind the form surface. This suppresses the adverse effect of the hydrophobic component that inhibits paint adhesion when paint is applied to the demolded concrete surface, and provides excellent paint adhesion. In addition, since the release agent for forms of the present invention does not contain any volatile components that cause odor as essential components, it does not harm the health of workers and improves workability. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a schematic diagram for explaining an apparatus used for evaluating the demoldability of concrete. [Diagram 2] 1 is a photograph showing the state immediately after application of a release agent 1 of an embodiment to the inner surface of a mold. [Diagram 3] 1 is a photograph of the surface of a mortar block after a smoothness test using a release agent 1 of an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described. The release agent for molds of the present invention is made of (1) N-octylpyrrolidone, (2) a kinetic viscosity at 40° C. of 30 to 120 mm 2 / s, and (3) an antistatic agent.
[0016] (1) N-octylpyrrolidone used in the present invention is typically represented by the following chemical formula.
[0017] [ka]
[0018] The base oil (2) used in the present invention has a kinetic viscosity of 30 mm at 40°C. 2 / s or more 120mm 2 Specific methods for measuring the kinetic viscosity include, for example, the methods described in JIS K2283-2000 and ASTM D445. 2 If the thickness is less than 120 mm / s, the thickness of the release agent applied to the surface of the steel formwork is too thin, resulting in a decrease in the smoothness and design of the concrete surface after removal from the formwork, and a decrease in the cleanability of the formwork. 2 If the rate exceeds 1 / s, a film will be formed inside the formwork after the concrete is poured, which will promote the formation of air bubbles inside the formwork. In the present invention, (2) the kinetic viscosity of the base oil at 40°C is 40mm 2 / s or more 110mm 2 / s or less is preferable, 40 mm 2 / s or more 70mm 2In addition, when a plurality of base oils are used, the kinematic viscosity specified in the present invention is the average value of the kinematic viscosities of the respective base oils. (2) The type of base oil is not particularly limited as long as it satisfies the above-mentioned kinematic viscosity range, and examples of the base oil include paraffinic oil, naphthenic oil, etc. (2) As the base oil, commercially available products can be used as appropriate. The (2) base oil used in the present invention, by defining the kinetic viscosity at 40°C as described above, can provide sufficient release properties over a wide range of environmental temperatures during work, and can suppress the generation of air bubbles in the formwork after the concrete is poured, thereby imparting good smoothness to the product. The base oil (2) used in the present invention is preferably a naphthenic oil. Naphthenic oils easily dissolve other components contained in the release agent for forms of the present invention, and can provide a wide range of freedom in blend design. Among them, naphthenic oils with a %CN of 40 or more in the ring analysis by the ndM method are preferred in order to further enhance the above-mentioned effects, and a %CN of 40 to 60 is even more preferred.
[0019] The form release agent of the present invention contains an antistatic agent (3), which is effective in removing air bubbles generated in the form after concrete is poured, and also suppresses static electricity generated during demolding, allowing the concrete to be demolded smoothly, thereby improving the smoothness of the surface of the PC member, for example. (3) The antistatic agent is not particularly limited, but cationic antistatic agents such as quaternary ammonium salts, for example, alkyltrimethylammonium salts, are particularly preferred.
[0020] The release agent for a form of the present invention may contain a diluent (4) as required. The diluent has the effect of improving the ease of application of the release agent for a form of the internal surface of the form. (4) Diluents include various industrial solvents, light oil, kerosene, etc., of which kerosene is preferred.
[0021] The mold release agent for molds of the present invention may further contain a fluorosurfactant and / or a silicone surfactant as a release aid (5). In the fluorosurfactant and / or silicone surfactant (5) used in the present invention, examples of the fluorosurfactant include perfluoroalkyl alkylene oxide adducts, perfluoroalkyl group-containing oligomers, perfluoroalkyl phosphate esters, perfluoroalkyl carboxylate esters, perfluoroalkyl quaternary ammonium salts, perfluoroalkyl amine oxide compounds, and perfluoroalkyl betaines. The fluorosurfactant is preferably a nonionic fluorosurfactant, and examples of the fluorosurfactant include perfluoroalkyl alkylene oxide adducts and perfluoroalkyl group-containing oligomers. Examples of commercially available fluorosurfactants include the Surflon series manufactured by AGC Seimi Chemical Co., Ltd. Examples of silicone surfactants include polyalkylphenylsiloxane, alkyl-modified silicone oil, polyether-modified silicone oil, polyalkylsiloxane, polymethylsilsesquioxane, polyalkylhydrogensiloxane, polyalkylalkenylsiloxane, polymethylphenylsiloxane, aralkyl-modified silicone oil, polydimethylsiloxane, alkylaralkyl-modified silicone oil, etc. Examples of commercially available silicone compounds include KF and KM series manufactured by Shin-Etsu Chemical Co., Ltd.
[0022] From the viewpoint of improving the effects of the present invention, when the total amount of the release agent for a form of the present invention is taken as 100 mass %, The proportion of the (1) N-octylpyrrolidone is 1 to 10 mass%, preferably 1 to 5 mass%; the proportion of the (2) base oil is 40 to 90 mass%, preferably 50 to 70 mass%; The proportion of the (3) antistatic agent is 1 to 10% by mass, preferably 1 to 5% by mass, and the remainder (if any) is preferably the (4) diluent and other additives. (5) The content of the release aid is preferably from 1 to 5% by mass, and more preferably from 1 to 3% by mass. When the content of each component falls within the above-mentioned limited range, extremely excellent properties can be exhibited with respect to the above-mentioned mold releasability, cleanability, smoothness, paint adhesion and workability.
[0023] The release agent for molds of the present invention may contain other additives as necessary. Examples of other additives include alcohols, waxes, emulsifiers, preservatives, etc., and these can be used in an appropriate amount within a range that does not impair the desired effects of the present invention.
[0024] The present invention also provides a method for casting a hydraulic composition, comprising the steps of applying the form release agent of the present invention to the inner surface of a form and casting a hydraulic composition thereon.
[0025] The hydraulic composition may, for example, be a composition containing hydraulic powder, aggregate, water, and other known additives.
[0026] Examples of hydraulic powder include cement, such as ordinary Portland cement, high-early-strength Portland cement, and ultra-high-early-strength Portland cement. In addition, gypsum, blast furnace slag, fly ash, silica fume, and the like can also be used. Examples of aggregate include fine aggregate and coarse aggregate, and the fine aggregate ratio is, for example, about 42 to 50%, and the amount of coarse aggregate used is, for example, 850 to 1000 kg / m 3 The water-cement ratio (W / C) is 55% or less. The hydraulic composition may be concrete containing fine aggregate and coarse aggregate as aggregates, or mortar containing fine aggregate as aggregates. The hydraulic composition may also contain various additives such as a dispersant, an antifoaming agent, an air-enhancing agent, a retarder, a foaming agent, a thickener, a foaming agent, a waterproofing agent, a fluidizing agent, and an early strength agent.
[0027] In the present invention, the material of the formwork is not particularly limited, but it is preferable that the formwork is made of steel, for example.
[0028] In the present invention, there is no particular limitation on the type of concrete to be poured into the formwork, but suitable concrete includes ordinary concrete, lightweight concrete, ultra-lightweight concrete, high-strength concrete, high-fluidity concrete, high-strength and high-fluidity concrete, fiber-reinforced concrete, etc. Also usable are high-fluidity mortar, high-strength mortar, fiber-reinforced mortar, etc.
[0029] The release agent for formwork of the present invention can be applied to the inner surface of the formwork using a brush, mop, spray, or the like. The amount of application may be any amount obvious to those skilled in the art, but may be, for example, 10 to 250 g / m 2 It is.
[0030] The hardening of the hydraulic composition may be performed according to a known method, with the temperature being kept at 2° C. or higher as the curing condition, and the curing time before demolding may be, for example, 24 to 72 hours. EXAMPLES
[0031] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.
[0032] (Preparation of various release agents) Based on the compositions (parts by mass) shown in Tables 1 and 2 below, various release agents for molds were prepared.
[0033] (Releasability test) A mortar of the following composition was prepared: Cement: Ordinary Portland cement Fine aggregate: JIS R 5201 standard sand Dispersant: None Amount of fine aggregate: 2 times the mass of cement Water-cement ratio (W / C): 50% by mass The above raw materials were mixed in a mixer to obtain a mortar. Next, the releasability of the mortar was evaluated using a shear adhesion evaluation device shown in Fig. 1. The shear adhesion evaluation device 1 has a base 10 and a pillar 11 erected on the base 10. A dolly 12 is placed on the base 10, and a steel test plate 13 is fixed on the dolly 12. A motor 14 and a load cell 15 are provided on the pillar 11, and the motor 14 and an end part C of the test plate 13 are connected by a wire 17 via a roller 16. The releasability test is carried out as follows. The test plate 13 is used as the bottom formwork, and an appropriate amount of each type of release agent shown in Tables 1 and 2 is applied thereto, and the mortar prepared above is poured thereon. After pouring, the mortar is subjected to moist air curing for 24 hours to harden, and a mortar block 18 is obtained. The motor 14 is operated to pull the test plate 13 in the direction of the arrow at a pulling speed of 1 mm / s, and the mortar block 18 is brought into contact with a stopper 19. The maximum load when the mortar block 18 is released from the test plate 13 is measured by the load cell 15. The shear adhesion is calculated by dividing the maximum load by the base area of the mortar, as shown in the following formula, to determine the adhesion per unit area of the mortar. The mortar block 18 is cubic in shape and has a base area of 25 cm. 2 or 100cm 2 and is 10cm tall. Shear adhesion (kg / cm 2 ) = Maximum load (kgf) / Mortar block base area The results are shown in Tables 1 and 2.
[0034] (Cleaning test) After the mold releasability test, the mortar block 18 was removed, and the surface of the bottom formwork of the test plate 13 constituting the bottom formwork was cleaned with a spatula-shaped scraper, and evaluated according to the following evaluation criteria. ◯: Easily cleanable (several cleaning operations with a scraping rod on the bottom formwork surface of the test plate 13 can remove almost all of the residue adhering to the surface). ×: Difficult to clean (even after the surface of the bottom formwork of the test panel 13 was cleaned several times with a scraping rod, a considerable amount of residue remained on the surface without being removed).
[0035] (Smoothness test) After the mold releasability test, the mortar block 18 was removed, and the surface condition of the mortar block 18 that had been in contact with the test plate 13 was visually observed and evaluated according to the following evaluation criteria. ◯: Smooth and aesthetically pleasing (almost no pitting or bubbles are visible on the surface of the mortar block 18). △: Slightly smooth, but slightly lacking in aesthetics (multiple pockmarks and air bubbles are observed on the surface of the mortar block 18). ×: Unevenness occurs and the appearance is lacking (a large number of pockmarks and bubbles are observed on the surface of the mortar block 18).
[0036] (Compatibility test) After preparation, each of the mold release agents was visually observed, and the compatibility was evaluated according to the following evaluation criteria. ◯: No separation of components observed, maintaining good emulsion state. ×: The components are separated.
[0037] (Paint adhesion test) Example 1 in Table 1 above and a Reference Example which is a conventional oil-based release agent were prepared. Subsequently, concrete was prepared having the following composition: Cement: Ordinary Portland cement Fine aggregate amount: 750~970kg / m 3 Coarse aggregate amount: 850~950kg / m 3 Dispersant content: 0.8 to 1.4% by mass based on cement Water-cement ratio (W / C): 40-50% by mass The above-mentioned raw materials were mixed in a mixer to obtain concrete.
[0038] The concrete was poured into a steel formwork to prepare a rectangular shaped sidewalk board with a length of 30 cm, a width of 30 cm, and a height of 5 cm. Before pouring the concrete, various formwork release agents were applied in appropriate amounts (100 g / m 2 ) or high volume (300g / m 2 ) was applied to the inner surface of the formwork. After the concrete was poured, it was allowed to harden for 24 hours to obtain various types of sidewalk boards. Next, multiple coats of paint were applied to one of the main surfaces of the sidewalk board as follows: Basecoat 1 → Basecoat 2 → Midcoat → Topcoat. The midcoats and topcoats were either strong solvent-based, weak solvent-based or water-based, and when a strong solvent-based midcoat was used, the topcoat was also strong solvent-based, when a weak solvent-based midcoat was used, the topcoat was also weak solvent-based, and when a water-based midcoat was used, the topcoat was also water-based. Basecoat 1 and basecoat 2 were water-based in all cases. Normally, the concrete surface is thoroughly wiped and roughened to remove any remaining release agent, but in this case, in order to conduct coating tests under more severe conditions, the concrete surface was only lightly wiped with a rag. Undercoat 1 (water-based): Undercoat PCW (AGC Coatec Co., Ltd., polyethylene resin emulsion, solid content (heating residue) 62.0 mass%, coating amount 0.1 to 0.15 kg / m 2 ) Undercoat 2 (water-based): Bonn HB Surfacer R (AGC Coatec Co., Ltd., acrylic resin emulsion paint, solid content (heating residue) 70.0 mass%, application amount 0.3 to 0.5 kg / m 2 ) Intermediate coat: Bonflon #1000HB intermediate coat (strong solvent-based), Bonflon Light intermediate coat (weak solvent-based), Bonflon Water-based #1500 intermediate coat (water-based). (All are manufactured by AGC Coatec Co., Ltd., acrylic urethane resin-based paint, solid content (heating residue) 62.0 mass%, application amount 0.11-0.14 kg / m 2 ) Topcoat: Bonflon GT-SR (strong solvent-based), Bonflon weak solvent enamel GT-SR (weak solvent-based), Bonflon water-based GT-SR (water-based). (All manufactured by AGC Coatec Co., Ltd., fluororesin paint, solid content (heating residue) 60.2 mass%, coating amount 0.08-0.09 kg / m 2 ) Each of the above applications was performed using a wool roller.
[0039] The sidewalk boards coated with the paint were stored under the following conditions. Condition 1: Stationary conditions (storage in air at room temperature for one month). Condition 2: Repeated hot and cold cycles (storage in water at 23°C for 18 hours → removal from water and storage at 50°C for 3 hours → storage at -20°C for 3 hours; this cycle is repeated 10 times).
[0040] The following experiment was conducted in accordance with JIS A 6909 Adhesion Strength Test for Architectural Finish Coating Materials. After storage under conditions 1 or 2, a 40 mm square steel attachment was attached to the painted surface of the sidewalk board with adhesive, a cut was made along the attachment that reached the base material, and the attachment was pulled using a Kenken adhesive strength tester to measure the adhesive strength (N / mm 2 ) was measured. The state of destruction was also observed. The results are shown in Table 3.
[0041] (Workability test) In the paint adhesion test, it was confirmed whether an odor was emitted during the work of applying the release agent to the inside surface of the formwork, and the results were evaluated according to the following evaluation criteria. The results are shown in Table 3. O: No odor. △: There is a slight odor.
[0042] In Table 3, the reference examples are examples in which a conventional oil-based release agent (outside the scope of the present invention) was used.
[0043] [Table 1]
[0044] [Table 2]
[0045] [Table 3]
[0046] The formwork release agent of the present invention caused the base material to break after painting, which indicates that the paint has good adhesion. On the other hand, the conventional product caused peeling at the interface between the coating film and the concrete substrate surface, which raises concerns about the influence of the remaining release agent. From the results of Tables 1 to 3, the form release agent of the present invention shows excellent properties in terms of releasability, cleanability, smoothness, paint adhesion and workability. Figure 2 is a photograph showing the state immediately after the form release agent of Example 1 was applied to the inner surface of the form, and sufficient wettability can be confirmed. FIG. 3 is a photograph of the surface of a mortar block after the smoothness test using the form release agent of Example 1, and sufficient smoothness can be confirmed. [Explanation of symbols]
[0047] 1. Shear adhesion evaluation device 10 Pedestal 11 Pillars 12 Trolley 13 Test plate 14 Motor 15 Load Cell 16. Lola 17 Wire 18 Mortar Block 19 Stopper
Claims
1. (1) N-octylpyrrolidone, (2) a kinetic viscosity at 40°C of 30 to 120 mm 2 and (3) an antistatic agent.
2. (4) The form release agent according to claim 1, further comprising a diluent.
3. (5) The release agent for a form according to claim 1, further comprising a fluorine-based surfactant and / or a silicone-based surfactant as a release aid.
4. 3. The form release agent according to claim 2, wherein, when the total amount of the form release agent is taken as 100% by mass, the content of the (1) N-octylpyrrolidone is 1 to 10% by mass, the content of the (2) base oil is 40 to 90% by mass, the content of the (3) antistatic agent is 1 to 10% by mass, and the remainder is the (4) diluent and other additives.
5. 4. The form release agent according to claim 3, wherein the proportion of the fluorine-based surfactant and / or the silicone-based surfactant (5) is 0.1 to 5 mass % when the total amount of the form release agent is 100 mass %.
6. (1) N-octylpyrrolidone, (2) a kinetic viscosity at 40°C of 30 to 120 mm 2 and (3) an antistatic agent, which is capable of producing a concrete product or mortar product having excellent smoothness.
7. 10. A method for casting a hydraulic composition, comprising the steps of applying the form release agent according to claim 1 or 6 to an inner surface of a form, and casting a hydraulic composition thereon.
Citation Information
Patent Citations
Form releasing agent for hydraulic composition
JP2023009801A